The Appearance of Cocoa Clones Tolerant to Infection Phytophthora palmivora - Ediwirman Ediwirman (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Cocoa pod rot (PBK) is the main disease that attacks cocoa pods caused by P. palmivora. Fruit rot disease causes loss of cocoa yield. Cocoa pod rot disease caused by P. palmivora pathogen is not a good and stable control method. One strategy that can be used for control is to develop superior clones tolerant of P. palmivora. Breeding program to obtain P. palmivora tolerant cocoa clones by utilizing cocoa genetic resources derived from potential cultivated clones through detached pot test. The study aimed to obtain cocoa pods tolerant of pod rot using the detached pod test. The research was conducted at the Phytopathology Laboratory of the Department of Plant Pests and Diseases, Faculty of Agriculture, Andalas University. The tested cocoa clones consisted of 6 clones, e.g., Sca 12, TSH 858, ICS 60, GC 7, K TSH 858, and K ICS 60. Cocoa clones were collected from a cocoa plantation owned by PT. Host Sari Lubuk Basuk-Agam Regency. The observed variables related to P. palmivora tolerant cocoa clones were; incubation period, growth of cacao fruit spot area, and color of cocoa beans. The results showed that the TSH 858 and ICS 60 clones had an incubation period of 3 DAI, while the Sca 12, ICS 60, GC 7, K TSH 858, and K ICS 60 clones had an incubation period of 2 DAI. The TSH 858 clone grew 10.82 cm2.day 1, while the ICS 60, GC 7, K. TSH 858 and K. ICS 60 clones grew in spot area, respectively; 11.42, 12.95, 13.24 and 13.58 cm2.day-1. TSH 858 clone has potential as a tolerant clone to P. palmivora attack through detached pod test on fruit.